Successful transcatheter aortic valve replacement in a patient with radiation-induced aortic stenosis - D. D. Zubarev; S. V. Sim; V. S. Krasnov; A. V. Gorbatykh; M. A. Chernyavsky; A. A. Prokhorikhin (Российский кардиологический журнал)
Aortic stenosis is one of the most common valvular heart defects that occurs in patients with oncology after radiation therapy and requires surgical treatment. However, this group of patients has a higher risk of intra- and postoperative complications, and therefore the most optimal method of surgical treatment of aortic stenosis in such a cohort of patients is transcatheter aortic valve implantation (TAVI).Brief description. Forty-six-year old woman entered the Almazov National Medical Research Center with a clinical picture of severe aortic stenosis. At a young age, the patient was diagnosed with lymphogranulomatosis, or Hodgkin’s disease, for which radiation therapy was performed, which was complicated in the long term by valvular pathology. After a thorough examination, a high intraoperative risk for the patient was determined by the cardiac team and endovascular treatment of severe aortic stenosis was performed. The postoperative period was complicated by the development of complete atrioventricular block, which caused the implantation of a permanent dual-chamber pacemaker.Discussion. The presented case is an example of successful surgical treatment of aortic stenosis associated with previous radiation therapy for Hodgkin’s disease in a patient.Conclusion. Endovascular aortic valve implantation is a promising approach to the treatment of patients with post-radiation aortic stenosis, since it is associated with unfavorable anatomical and clinical risk factors for surgical valve replacement. Despite their younger age, these patients represent a category of higher surgical risk. Therefore, additional attention should be paid to the planning of the procedure and the prevention of the main TAVI risks.